Reliability and Accuracy of Standard Reference Procedures for Measurements of Trunk and Arm Postures in Ergonomics - Carl M. Lind; Ida-Märta Rhen; Mikael Forsman (Bioengineering)
Adequate reference procedures for obtaining the reference zero-angle position are important for precise and accurate posture measurements, but few studies have systematically investigated these. A limited number of previous studies suggest differences in accuracy between procedures, with some causing an underestimation of the true arm elevation angle when sensors are taped to the skin. The reliability of commonly used reference procedures for the measurement of the trunk posture is also not well explored, and alternative procedures may improve precision. Based on this identified gap, this study evaluated the test–retest reliability of the N-position (I-pose), i.e., the standard procedure for recording trunk postures, and compared it with two new alternative procedures. Additionally, the accuracy of the N-position for measuring arm elevation angles was compared with one alternative procedure. A total of 40 participants (22 women and 18 men) aged 26–70 years performed the reference procedures in a laboratory setting. Postures were recorded using a smart workwear system equipped with two inertial measurement units (IMUs) embedded in pockets within the workwear. For the trunk posture, the N-position showed a slight lack of test–retest reliability, while one of the alternative procedures demonstrated better test–retest reliability. For the arm posture, the N-position, which does not include lateral trunk inclination, resulted in a substantial underestimation of the arm elevation angle of approximately 15°, which is a novel finding. In contrast, the posture involving trunk inclination closely matched the targeted reference, with a difference of less than 2°. This study underscores the importance of selecting appropriate reference procedures to ensure precise and accurate posture measurements.